Soil seedbank in integrated crop-pasture systems - Ikeda, Fernanda Satie; Mitja, Danielle; Vilela, Lourival; Carmona, Ricardo (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this study was to evaluate the effects of cultivation and tillage systems, and fertilization level, on soil seedbanks of areas submitted to: three cultivation systems – continuous crop (L), crop-pasture-crop (LPL), pasture-crop-pasture (PLP); two tillage systems – tillage (C) and no-tillage (D); two fertilization levels – maintenance (1) and gradual corrective (2); and a continuous pasture area under tillage and gradual corrective fertilization. Seed density of crop-pasture cultivation systems, was lower than in continuous crop, and higher compared to continuous pasture system, except for LPLC1 and LPLC2 cultivated areas. The seedbanks in continuous cropping areas was lower in no-tillage than in tillage system areas, but in PLP areas with gradual corrective fertilization, there was no difference between tillage systems. The fertilization level caused a reduction in seed density only in LPLC and PLPC cultivated areas. Integrated crop-pasture system with no-tillage adoption can be useful in weed management of grains crop areas.
Keywords: fertilization; Cerrado; integrated crop-livestock; weed; tillage; no-tillage